2020
DOI: 10.3390/nano10061225
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet Photodetection Based on High-Performance Co-Plus-Ni Doped ZnO Nanorods Grown by Hydrothermal Method on Transparent Plastic Substrate

Abstract: A growth scheme at a low processing temperature for high crystalline-quality of ZnO nanostructures can be a prime stepping stone for the future of various optoelectronic devices manufactured on transparent plastic substrates. In this study, ZnO nanorods (NRs) grown by the hydrothermal method at 150 °C through doping of transition metals (TMs), such as Co, Ni, or Co-plus-Ni, on polyethylene terephthalate substrates were investigated by various surface analysis methods. The TM dopants in ZnO NRs suppressed the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 62 publications
0
39
0
Order By: Relevance
“…The investigation of ZnO crystals and thin films has attracted great interest in the field of solid-state optoelectronics [ 1 ]. Its optical properties, electrical conductivity and radiation hardness make ZnO a good candidate for transparent thin-film transistors, laser diodes, light emitting diodes and photodetectors [ 2 , 4 , 5 ]. In particular, ZnO is promising for photonic applications in the UV and blue spectral range [ 3 , 6 ] based on exciton emission even at room temperature (RT) because of its wide band gap (~3.4 eV [ 1 ]) and large excitonic binding energy (~60 meV [ 7 ]), that is about 2.4 times higher than thermal energy (k B T) at 298 K. Ferromagnetism at RT has been observed in ZnO doped with transition metals leading to potential application in spintronics devices [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The investigation of ZnO crystals and thin films has attracted great interest in the field of solid-state optoelectronics [ 1 ]. Its optical properties, electrical conductivity and radiation hardness make ZnO a good candidate for transparent thin-film transistors, laser diodes, light emitting diodes and photodetectors [ 2 , 4 , 5 ]. In particular, ZnO is promising for photonic applications in the UV and blue spectral range [ 3 , 6 ] based on exciton emission even at room temperature (RT) because of its wide band gap (~3.4 eV [ 1 ]) and large excitonic binding energy (~60 meV [ 7 ]), that is about 2.4 times higher than thermal energy (k B T) at 298 K. Ferromagnetism at RT has been observed in ZnO doped with transition metals leading to potential application in spintronics devices [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…By investigating the relationship between diffusion coefficient and oxygen partial pressure during the preparation of (Co,Cr,Fe,Mn,Ni) 3 O 4-y , Grzesik et al [55] concluded that oxygen content of the final product would be reduced at low oxygen partial pressure levels, implying that corresponding oxygen vacancy concentration would be higher than at high oxygen partial pressure. So, by means of controlling oxygen vacancies, we could regulate the devices' electrical performance [56].…”
Section: Electrical Propertiesmentioning
confidence: 99%
“…A highest spectral responsivity R of ~1.5 × 10 5 A/W was obtained from the PDs at a wavelength of 360 nm, as revealed in Figure 7, when plasma-treated for 6 min due to improvement in ZnO material quality. The UV sensing mechanism of the IDE pattern-based PDs is based on the modulated photoconduction through the crosslinked NR-NR bridges caused by O2 adsorption and desorption on the NR surface [28]. In the dark state, expanded ZnO surface depletion caused by O2 -adsorption brings about a minimum cross-section of conducting area and leads to a small dark current flowing inside the NR.…”
Section: Cooh + No * → N O + Co + H Omentioning
confidence: 99%
“…Figure 8. I-V characteristics of (a) the HEMT-based and (b) IDE pattern-based UV PDs.The UV sensing mechanism of the IDE pattern-based PDs is based on the modulated photoconduction through the crosslinked NR-NR bridges caused by O 2 adsorption and desorption on the NR surface[28]. In the dark state, expanded ZnO surface depletion caused by O 2 adsorption brings about a minimum cross-section of conducting area and leads to a small dark current flowing inside the NR.…”
mentioning
confidence: 99%